TECHNOLOGY FOR THE DEVELOPMENT OF COGNITIVE ACTIVITY OF STUDENTS IN THE PROCESS OF TEACHING A FOREIGN LANGUAGE - Xurramov, Eshmaxmat (Журнал иностранных языков и лингвистики, 2021)
The development of students' cognitive activity depends on the correct interaction of all elements of the pedagogical process: goals, content, means and methods of teaching, a rationally structured system of classes in a foreign language, including classroom, home, independent and laboratory work on the language. A significant role in the development of students' cognitive activity is played by a foreign language lesson, which must meet didactic requirements, i.e. to be built taking into account the unity of teaching and development, to be scientific in the nature of the content of the educational material and in the way of its assimilation. Cognitive activity in the educational process is a single process of generating students' thoughts and speech, this constitutes the material basis of education. Mastering by students the basics of teaching, direct and indirect, is today the main practical goal. This necessitates a deep study of the process of development of cognitive activity in search of opportunities for its activation. This circumstance determined the choice of the topic of our thesis research.